2019
DOI: 10.1007/s00192-019-03918-9
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse patients’ attitudes and preferences regarding their uterus: comparing German- and Russian-speaking women

Abstract: Introduction and hypothesisThe aim of this study was to compare preferences of patients with pelvic organ prolapse (POP) regarding their uterus between German- and Russian-speaking areas.MethodsSix urogynecologic tertiary referral centers participated in this prospective study: three centers from German-speaking countries and three from different regions of Russia. To assess the uterus-related preferences as well as the attitude toward hysterectomy versus uterus-sparing prolapse surgery, we developed a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In fact, this operation can be considered as an "organ amputation", which makes it di cult to accept, in addition to the symbolic value of the uterus. Indeed, its loss would be synonymous with the loss of femininity and reproductive capacity, which would have a heavy psychological impact [36]. On the other hand, the disappearance of menstruation after surgery can be experienced as a loss of sexual identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this operation can be considered as an "organ amputation", which makes it di cult to accept, in addition to the symbolic value of the uterus. Indeed, its loss would be synonymous with the loss of femininity and reproductive capacity, which would have a heavy psychological impact [36]. On the other hand, the disappearance of menstruation after surgery can be experienced as a loss of sexual identity.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal dryness is frequently described in patients. It is explained by estrogen de ciency and by iatrogenic lesions of the autonomic innervation pathways responsible for the innervation of the vagina [5,36]. Its frequency is much greater in postmenopausal patients or those who have had bilateral adnexectomy [22,28].…”
Section: Discussionmentioning
confidence: 99%
“… 17 In addition, when non-inferior outcomes are guaranteed, it is widely accepted how women do prefer to avoid concomitant hysterectomy. 18 , 19 Third, treating uterine prolapse by removing the organ could be detrimental, as it may raise the complications rate, while it just represents a passive element of POP pathogenesis, rather than its cause. 20 In our experience, uterus-sparing RSCP provided perioperative and functional outcomes consistent with those reported in current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the rejection of a hysterectomy included a sense of feeling older, plus sadness about losing fertility and body image due to the removal of the uterus. Different preferences regarding uterine preservation were found among populations: 31% among Hispanics, 40% among Germans, and 54% among Russians [59,60]. It was found that being older was a positive predictor of the decision to undergo a hysterectomy: compared with younger women below 40 years of age, women aged 45 to 49 years were less likely to use alternative treatments prior to a hysterectomy (OR 0.41; 95% CI: 0.21-0.76) [61].…”
Section: Fertility-sparing Treatment Vs Less Radical Treatment: Treat...mentioning
confidence: 99%